2013
DOI: 10.1673/031.013.0401
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of the Red-Belted Clearwing Moth,Synanthedon myopaeformis, and its ParasitoidLiotryphon crassisetain Apple Orchards in Yellow Moericke Traps

Abstract: This study was conducted in 2008–2010 in three apple orchards in western Poland and involved a massive catch of the red-belted clearwing moth, Synanthedon myopaeformis (Borkhausen) (Lepidoptera: Sesiidae), and its parasitoid Liotryphon crassiseta (Thomson) (Hymenoptera: Ichneumonidae) in yellow Moericke traps. The flight time for both species was correlated and fell in the first half of July. However, the correlation between the occurrences of both species was statistically significant only in 2008, when most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
0
6
1
Order By: Relevance
“…These traps have been used in studies of parasitoids in in a variety of habitats including agroecosystems and other cultivated habitats. For instance, Liotryphon crassiseta (Thomson), an ichneumonid parasitoid of the red-belted clearwing moth, Synanthedon myopaeformis (Borkhausen), was monitored using yellow pan traps in apple orchards of western Poland [157]. Malaise traps were used to compare relative abundance of parasitoids in herbicide-treated and untreated loblolly pine ( Pinus taeda L.) plantations in the coastal plain of Georgia, USA [158].…”
Section: Natural Enemies/pest Managementmentioning
confidence: 99%
“…These traps have been used in studies of parasitoids in in a variety of habitats including agroecosystems and other cultivated habitats. For instance, Liotryphon crassiseta (Thomson), an ichneumonid parasitoid of the red-belted clearwing moth, Synanthedon myopaeformis (Borkhausen), was monitored using yellow pan traps in apple orchards of western Poland [157]. Malaise traps were used to compare relative abundance of parasitoids in herbicide-treated and untreated loblolly pine ( Pinus taeda L.) plantations in the coastal plain of Georgia, USA [158].…”
Section: Natural Enemies/pest Managementmentioning
confidence: 99%
“…For example, the beginning of flight varied 34 days, and the termination of flight varied 32 days in particular years. Similarly, Bąkowski et al (2013) found in western Poland a high variability (exceeding 30 days) in the beginning of S. myopaeformis flight from year to year. In contrast, Kutinkova et al (2006) found a very low variability in the beginning of flight from year to year in the Plovdiv region in Bulgaria.…”
Section: Discussionmentioning
confidence: 63%
“…The present results are somewhat in agreement with Tadros (1977), who stated that emergence of S. myopaeformis moths highly affected with the temperature but the relative humidity had less effect. Also, Bąkowski et al (2013) in western Poland, conducted a monitoring study of S. myopaeformis moths in apple orchards and proved that in January and February 2008, the average mean temperatures were considerably higher than in 2009 and 2010, which undoubtedly could have affected the survival of caterpillars in winter in apple orchards.…”
Section: Effect Of Weather Factors On Moths Activitymentioning
confidence: 99%